2021
DOI: 10.21608/aasj.2021.186453
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intercropping and plant distribution of sorghum with soybean on growth and yield of Sorghum bicolor

Abstract: This field experiment was carried out at special farm at Luxor governorate, Egypt during 2018 and 2019 seasons to study the effect of some intercropping patterns and plant distributions of sorghum (var. Dorado) and soybean (var. Giza-111) on the growth, yield and yield components and the economic return of the sorghum plants. The experimental was laid out in split-split plot with randomized block design in three replications. The plant height of sorghum was significant affected by the different intercropping p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…The results further indicated that the LER was influenced by the density of cowpea as well as the grain sorghum cultivar in intercrop at each experimental site. LER variation due to mixture in various planting patterns has also been reported elsewhere [28,41,42]. The high LER observed in this study was due to the efficient use of resources such as light, water, and nitrogen between grain sorghum cultivars and cowpea [43].…”
Section: Discussionsupporting
confidence: 74%
“…The results further indicated that the LER was influenced by the density of cowpea as well as the grain sorghum cultivar in intercrop at each experimental site. LER variation due to mixture in various planting patterns has also been reported elsewhere [28,41,42]. The high LER observed in this study was due to the efficient use of resources such as light, water, and nitrogen between grain sorghum cultivars and cowpea [43].…”
Section: Discussionsupporting
confidence: 74%